Fusaric acid instigates the invasion of banana by Fusarium oxysporum f. sp. cubense TR4. Issue 2 (24th October 2019) - Liu, Siwen; Li, Jian; Zhang, Yong; Liu, Na; Viljoen, Altus; Mostert, Diane; Zuo, Cunwu; Hu, Chunhua; Bi, Fangcheng; Gao, Huijun; Sheng, Ou; Deng, Guiming; et al.
Summary: Fusaric acid (FSA) is a phytotoxin produced by several Fusarium species and has been associated with plant disease development, although its role is still not well understood. Mutation of key genes in the FSA biosynthetic gene ( FUB ) cluster in Fusarium oxysporum f. sp. cubense tropical race 4 ( Foc TR4) reduced the FSA production, and resulted in decreased disease symptoms and reduced fungal biomass in the host banana plants. When pretreated with FSA, both banana leaves and pseudostems exhibited increased sensitivity to Foc TR4 invasion. Banana embryogenic cell suspensions (ECSs) treated with FSA exhibited a lower rate of O2 uptake, loss of mitochondrial membrane potential, increased reactive oxygen species (ROS) accumulation, and greater nuclear condensation and cell death. Consistently, transcriptomic analysis of FSA‐treated ECSs showed that FSA may induce plant cell death through regulating the expression of genes involved in mitochondrial functions. The results herein demonstrated that the FSA from Foc TR4 functions as a positive virulence factor and acts at the early stage of the disease development before the appearance of the fungal hyphae in the infected tissues.